2007
DOI: 10.1002/jhet.5570440110
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthesis of some new benzoyl‐substituted heterocycles from 2‐benzoyl‐3‐phenylpent‐2‐ene‐1,5‐dinitrile

Abstract: 2‐Benzoyl‐3‐phenylpent‐2‐ene‐1,5‐dinitrile 1 undergoes bromination with N‐bromosuccinimide (NBS) to afford the bromo derivative 2a. This bromo derivative undergoes reactions with sodium hydrogen sulfide, ethyl thioglycollate, hydroxylamine hydrochloride, hydrazines, cyanoacetamide, cyanacetohydrazide and urea derivatives to afford the thiophene 4, 4H‐thiopyran 6, 4H‐1,2‐oxazine 8, 4H‐pyridazines 10a,b, the pyridine 15, pyrrolo[1,2‐b]pyridazine 17 and the N‐substituted‐pyrrole derivatives 19a‐c respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Mehdi Ghandi et al [7] in 2015 reported a series of quinolinyl-1,4-dihydropyridines, where the À NH 2 proton peak was shown to appear around 6.36-6.43 ppm as a broad singlet. In another report, [27] for 4-aryl-1,4-dihydropyridine À NH 2 proton peak appeared at 7.85 ppm as a broad singlet. In 2014 Chetan B. Snagani et al reported a series of quinolinyl-1,4-dihydropyridines in which À NH 2 proton peak was shown to appear around 7.08 ppm as a singlet.…”
Section: Synthesis and Characterization Of Quinolinyl-14-dihydropyrimentioning
confidence: 88%
“…Mehdi Ghandi et al [7] in 2015 reported a series of quinolinyl-1,4-dihydropyridines, where the À NH 2 proton peak was shown to appear around 6.36-6.43 ppm as a broad singlet. In another report, [27] for 4-aryl-1,4-dihydropyridine À NH 2 proton peak appeared at 7.85 ppm as a broad singlet. In 2014 Chetan B. Snagani et al reported a series of quinolinyl-1,4-dihydropyridines in which À NH 2 proton peak was shown to appear around 7.08 ppm as a singlet.…”
Section: Synthesis and Characterization Of Quinolinyl-14-dihydropyrimentioning
confidence: 88%
“…In the past decade, we have been involved in a program aiming at the synthesis of new heterocyclic compounds that may possess biologically active properties to be used as potential biodegradable agrochemicals [2–5]. In continuation of our earlier interest in 3(5)‐aminopyrazole, we report here an efficient synthesis of the hitherto unreported ethyl 5‐amino‐3‐phenyl‐1 H ‐pyrazole‐4‐carboxylate 3 and its exploitation for the synthesis of some new fused pyrazole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, we have been involved in a program aimed at the synthesis of some new heterocyclic systems of biological interest to be tested as biodegradable agrochemicals . In the context of this program, we have previously reported several syntheses starting from 2‐bromo‐1‐phenylethanone (ω‐bromoacetophenone) 2a (obtained from acetophenone 1 by bromination; Fig.…”
Section: Introductionmentioning
confidence: 99%